2017
DOI: 10.15171/ps.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics of Liposomal Formulation Dispersed in HPMC Matrix and Freeze-Dried Using Maltodextrin and Mannitol as Lyoprotectant

Abstract: Background: The present study aims to design formulation of liposomes that are well-preserved during freeze-drying. The combination of Hydroxy Propyl Methyl Cellulose (HPMC) as dispersion matrix and lyoprotectants; maltodextrin or mannitol, was employed to prevent aggregation and/or recrystallization. The obtained dry products were investigated in terms of their physical characteristics. Methods: Liposomes were prepared using thin film method and hydrated with the lyoprotectant solution. The formed liposomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The saturated sucrose in the mixture has been suggested to increase the tendency of internal interactions; however, the molecular dynamics were not sufficient to recrystallize. 40,41 It can be confirmed that casein, as well as sucrose in the developed MC-SDP formulations, successfully prevented curcumin from recrystallization. Moreover, the employed ratio of polymeric casein and sucrose was sufficient to inhibit the crystallization of curcumin.…”
Section: Differential Thermal Analysismentioning
confidence: 81%
“…The saturated sucrose in the mixture has been suggested to increase the tendency of internal interactions; however, the molecular dynamics were not sufficient to recrystallize. 40,41 It can be confirmed that casein, as well as sucrose in the developed MC-SDP formulations, successfully prevented curcumin from recrystallization. Moreover, the employed ratio of polymeric casein and sucrose was sufficient to inhibit the crystallization of curcumin.…”
Section: Differential Thermal Analysismentioning
confidence: 81%
“…With the same manufacturing technique, the liposomes prepared using the SPC, EPC, and HSPC showed similar morphology that was spherical and homogeneously distributed in the porous solid gel matrix. Such porous structure might be initiated by the entrapped ice crystals that sublimated during the freeze-drying process and resulted in a hollow structure [ 32 , 33 ]. The entrapped liposomes were a few micrometers in size, which indicates that they aggregated during the incorporation into the solid gel matrix.…”
Section: Resultsmentioning
confidence: 99%
“…e ., 1:4, 1:8, 1:15 and 1:30 w/w , respectively). Maintaining liposomal integrity during freezing and subsequent drying is challenging [54]. Formation of ice crystals in the internal aqueous compartment or the external aqueous phase during the freezing step can rapture the liposomal lipid bilayers [55].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the applicability of using TFFD to formulate dry powders of AS01B-adjuvanted vaccines was investigated using OVA as a model antigen and different stabilizers (i.e., sucrose, trehalose, and mannitol) at different lipid to stabilizer ratios (i.e., 1:4, 1:8, 1:15 and 1:30 w/w, respectively). Maintaining liposomal integrity during freezing and subsequent drying is challenging [54]. Formation of ice crystals in the internal aqueous compartment or the external aqueous phase during the freezing step can rapture the liposomal lipid bilayers [55].…”
Section: Dry Powders Of As01b Adjuvant and As01b/ova Model Vaccinementioning
confidence: 99%